Teachers’ Attitude Toward Mathematics Classroom Discourse In Secondary Schools In Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
This study was designed to investigate the teachers’ attitude towards classroom discourse and how their attitude is associated with their classroom instructional practices. Their attitude was characterized by their conceptions about the nature of mathematics and their views about classroom discourse in the face of current reforms in mathematics. Mixed method research design was adopted. The study was based on theoretical frameworks of Vygotsky (1978) and Bruner (1986). The study was conducted in secondary schools in Vihiga County, Kenya. Proportionate stratified and simple random sampling techniques were used to select the sample. Data was collected using questionnaires, interview schedule and classroom observation checklist. Both descriptive and inferential statistics were used to analyze the data. The results of this study show that teachers in the control set ups tend to hold strong conceptions about mathematics that are consistent with the instrumental view. Their conceptions were not in line with the recommended reform approaches and have both desirable and undesirable consequences in the way teachers teach in the classroom. In view of the findings, it was recommended that in-order to gradually challenge the teachers’ negative conceptions about mathematical classroom discourse, adequate educational interventions should be planned and implemented in teacher education programmes to support the teachers in concretizing these conceptions.